Peran Pemerintah Desa dalam Meningkatkan Penerimaan Pajak Bumi dan Bangunan di Desa Sumorame - Syamsudyan, Muhammad; Agustina, Isna Fitria (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
This research arose from the low realization of PBB (land and building tax) despite the significant potential of village taxes. This study aims to analyze the role of the Sumorame Village Government, Candi District, Sidoarjo Regency in increasing Land and Building Tax (PBB) revenue. The study used a qualitative descriptive method with interview, observation, and documentation techniques, as well as data analysis using the Miles, Huberman, and Saldaña model. The results show that the village government has three main roles: regulator, dynamicator, and facilitator. As a regulator, the government sets policies and conducts tax socialization. As a dynamicator, the government motivates the community through innovative programs such as providing door prizes. As a facilitator, the government provides payment services through BUMDes and the jemput bola program. Obstacles faced include low public understanding, limited time, and suboptimal distribution of SPPT. Optimization of education, service innovation, and the use of technology are needed to improve compliance and PBB revenue.